Reducing Behavioral Constraints to Supplier Integration: A Socio‐Technical Systems Perspective. Issue 1 (22nd January 2013) - Kull, Thomas J.; Ellis, Scott C.; Narasimhan, Ram
<x xml:space="preserve">Abstract</x> Despite the benefits of supplier integration (SI), research suggests such collaborative initiatives are inhibited by behavioral constraints. While studies tend to advance technical reasons that hinder SI, we draw from socio‐technical system (STS) theory to suggest that the interaction among social, technical, and environmental features can give rise to behaviors that constrain SI. We conceptualize buying and supplying firms as two distinct social‐technical systems and SI as a merging of technical systems across firms. We posit that behavioral constraints, which limit the realization of SI goals, arise when technical integration commences without appropriate a priori consideration for the social or environmental implications of technical changes. Our conceptual development not only proposes specific social processes that increase the likelihood of behavioral constraints during SI, but also suggests technical approaches to prevent them. Further, we identify salient environmental contingencies affecting the emergence of behavioral constraints. By extending STS theory to the interorganizational context, we contribute to SI research by offering a holistic view of SI and proposing ways managers can address the challenges that exist.